STRATEGI KOMUNIKASI ANDCRAFT MELALUI MEDIA INSTAGRAM - Arsamevia, Tiara; Suryo, Herning; Mahar Rizqi, Fikriana (Solidaritas, 2025)
ABSTRACT The rapid development of information and communication technology has revolutionized the way humans communicate, interact and participate. Social media is one form of development of information and communication technology. Now social media is also utilized as a means of doing business. Instagram has become a popular platform for building audiences and promoting goods or services for businesses. Competition in the business world in utilizing Instagram as a communication medium is getting tighter, an understanding of communication and good communication planning is needed to be able to convey messages well and effectively. This research discusses the communication strategy carried out by Andcraft through Instagram media. The method used in this research with a qualitative approach, data collection with interviews, observation and documentation, and data validation used is miles and huberman interactive analysis. The results showed that Andcraft uses Instagram for planning to know the audience, create messages, determine methods and choose media. Utilizing Instagram as a communication medium is done by Andcraft by using photo and video features, comments, captions, hashtags, Instagram ads, and Instagram insight for social media maintenance of its account. However, in some cases Andcraft does not maximize some of the features that are a challenge for him. Keywords: Communication, Strategy Communication, Instagram, Instagram Utilization